Implementation of risk-based lipid-lowering therapies in older (age ≥ 65 years) and very-old adults (age ≥ 75 years) with ischemic heart disease in the greater Salzburg region - Kopp, Kristen; Motloch, Lukas J.; Wernly, Bernhard; Berezin, Alexander E.; Maringgele, Victoria; Dieplinger, Anna; Hoppe, Uta C.; Lichtenauer, Michael (Frontiers in Pharmacology, 2024)
European guidelines recommend implementation of lipid-lowering therapies (LLTs) in adults (> 65 years) with established atherosclerotic cardiovascular disease (ASCVD) and for risk-based primary prevention in older adults (< 75 years) yet their use in very-old adults (> 75 years) is controversial, discretionary, and oriented on the presence of risk factors. Aim of this retrospective study is to assess guideline-directed LLT implementation and LDL-C target achievement in high-/very-high-risk older/very-old adults (65-74, >75years) at presentation for ST-segment elevation myocardial infarction (STEMI), also to assess evidence-based care delivery to older adults in our region. Methods: All STEMI patients with available LDL-C and total cholesterol presenting for treatment at a large tertiary center in Salzburg, Austria 2018-2020 were screened (n=910). High-risk/very-highrisk patients (n=369) were classified according to European guidelines criteria and divided into cohorts by age: <65 years (n=152), 65-74 years (n=104), >75 years (n=113). Results: Despite high-/very-high-risk, prior LLT use was < 40% in the total cohort with no significant difference by age.Statin monotherapy predominated, 20-23% of older/ very-old adults in the entire cohort were using low-/moderate-intensity stains, 11-13% high-intensity statins, 4% ezetimibe therapy, none taking PCSK9 inhibitors. In the secondary prevention cohort, 53% of older/ very-old patients used prior LLTs. Significantly higher percentages of older/oldest ASCVD patients (43%, 49%) met LDL-C targets < 70 mg/dL compared to patients <65 years (29% p= 0.033), and just 22% and 30% attained stricter < 55 mg/dL LDL-C targets. Low LLT uptake (16%) among older adults 64-74 years for primary prevention resulted in 17% and 10% attainment of risk-based LDL-C targets < 70 mg/dL and < 55 mg/dL respectively. Oldest adults >75 years in both primary and secondary prevention groups more often met risk-based targets than older and younger adults, despite predominant low-/moderateintensity statin monotherapy. Conclusion: Secondary prevention was sub-optimal in our region. Less than half of older/ very-old adults with established ASCVD met LDL-C targets at time of STEMI, suggesting severe care-delivery deficits in LLT implementation. Shortcomings in initiation of riskbased LLTs were also observed among high-/very-high-risk primary prevention patients <75 years with achievement of risk-based LDL-C targets in 10-48% of these patients.